The Influence of Physical Activity, Knowledge, and Diet on The Incidence of Degenerative Diseases in The Gymnastics Community - Budhi Setianto (Jurnal Ilmiah Kesehatan)
According to statistics from the 2018 Basic Health Research, 65.7% of Indonesians